Systematic review and meta‑analysis of factors predicting postoperative lung function after lung cancer resection - Hongling Wang; Lihong He; Xiaoyun Hu; Gongxue Xian (Videosurgery and Other Miniinvasive Techniques)
Introduction: Lung resection continues to be the most effective treatment for early-stage lung cancer. Prediction of postoperative lung function is particularly important when evaluating patient eligibility for surgery, as it helps assess the likelihood of experiencing difficulty breathing after the operation.